2020
DOI: 10.1186/s12953-020-00162-8
|View full text |Cite
|
Sign up to set email alerts
|

Proteome-wide identification of arginine methylation in colorectal cancer tissues from patients

Abstract: Background: Protein arginine methylation reaction is catalyzed by protein arginine methyltransferase (PRMT) and the modification is implicated in various diseases including cancer. Currently, thousands of arginine methylation sites have been identified using high-resolution mass spectrometry-based proteomics technology. However, identification of arginine methylation using clinical samples at proteome level has not been reported yet. The objective of the present study was to identify, monomethyl-arginine (MMA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 38 publications
3
23
0
Order By: Relevance
“…Lastly, to further expand our knowledge of methylarginine containing proteins and the residues which are specifically modified, we compiled previously published publicly available methylarginine datasets ( Table S5 ) ( Fedoriw et al., 2019 ; Fong et al., 2019 ; Guo et al., 2014 ; Hornbeck et al., 2015 ; Larsen et al., 2016 ; Li et al., 2021 ; Lim et al., 2020 ; Musiani et al., 2019 ; Wei et al., 2020 ). Together, these data sets—including our own—contained 5,255 unique methylarginine-modified proteins with 15,386 independent methylarginine residues ( Figures S7 A and S7B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, to further expand our knowledge of methylarginine containing proteins and the residues which are specifically modified, we compiled previously published publicly available methylarginine datasets ( Table S5 ) ( Fedoriw et al., 2019 ; Fong et al., 2019 ; Guo et al., 2014 ; Hornbeck et al., 2015 ; Larsen et al., 2016 ; Li et al., 2021 ; Lim et al., 2020 ; Musiani et al., 2019 ; Wei et al., 2020 ). Together, these data sets—including our own—contained 5,255 unique methylarginine-modified proteins with 15,386 independent methylarginine residues ( Figures S7 A and S7B).…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, we compiled all publicly available data for the human arginine methylome ( Fedoriw et al., 2019 ; Fong et al., 2019 ; Guo et al., 2014 ; Hornbeck et al., 2015 ; Larsen et al., 2016 ; Li et al., 2021 ; Lim et al., 2020 ; Musiani et al., 2019 ; Wei et al., 2020 ) ( Table S5 ). Together these data exemplify the diverse array of PRMT substrates.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, proteome-wide strategies to study R-methylated proteins have been optimized, thanks to the implementation of efficient biochemical protocols for methyl-peptide enrichment, coupled to off-line high pH (HpH) chromatographic fractionation and high-resolution mass spectrometry (MS) analysis. Recently published evidence ( Fedoriw et al, 2019 ; Fong et al, 2019 ; Lim et al, 2020 ; Szewczyk et al, 2020 ), together with MS-proteomics analyses carried out in our group ( Musiani et al, 2019 ; Musiani et al, 2020 ; Spadotto et al, 2020 ), has shown that pharmacological and genetic inhibition of PRMTs coupled with quantitative MS-based analysis are powerful approaches to expand the knowledge about the extent of this modification, its dynamics upon different perturbation and its involvement in different cellular pathways. One interesting piece of information emerging from these studies is that RNA-binding proteins (RBPs) are over-represented among experimentally-annotated R-methylated proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Both types of post-translational methylation contribute to the exquisite control of gene expression through modification of histone proteins. Lys and Arg methylation also regulate a range of non-histone proteins including proteins involved in transcription and RNA-binding, translation, chaperone, cytoskeletal and membrane proteins and adaptor/scaffold proteins (Guo et al 2014 ; Lim et al 2020 ). However, there are several and important differences between the methylation of lysines and arginines.…”
Section: Arginine Methylation and Protein Arginine Methyltransferasesmentioning
confidence: 99%